2015
DOI: 10.1177/1541931215591362
|View full text |Cite
|
Sign up to set email alerts
|

Distraction Becomes Engagement in Automated Driving

Abstract: As vehicle automation proliferates, the current emphasis on preventing driver distraction needs to transition to maintaining driver availability. During automated driving, vehicle operators are likely to use brought-in devices to access entertainment and information. Do these media devices need to be controlled by the vehicle in order to manage driver attention? In a driving simulation study ( N=48) investigating driver performance shortly after transitions from automated to human control, we found that partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(59 citation statements)
references
References 15 publications
0
57
0
2
Order By: Relevance
“…As data shows, most subjects experience subjective drowsiness in less than 15 minutes. Albeit works such as [22], [26] suggest that performing engaging non-driving tasks can counter this effect, there is still no large scale experiment or high number of experiments confirming the validity.…”
Section: A Drowsiness In Conditional Automationmentioning
confidence: 99%
See 1 more Smart Citation
“…As data shows, most subjects experience subjective drowsiness in less than 15 minutes. Albeit works such as [22], [26] suggest that performing engaging non-driving tasks can counter this effect, there is still no large scale experiment or high number of experiments confirming the validity.…”
Section: A Drowsiness In Conditional Automationmentioning
confidence: 99%
“…Addressing specifically drowsiness signs, Miller et al [26] defines drowsiness indicators in terms of manual eye-closure for 5 seconds or yawning events. Results show that these events happen significant more when the driver needs to be in a supervision mode instead of being engaged with multimedia non-driving tasks.…”
Section: B Drowsy Driving Diagnosis and Effects In Camentioning
confidence: 99%
“…For example, it has been proposed to display the time left in automated mode and the confidence level of the automated vehicle to further enhance the safety and efficiency of transitions to manual driving [25][26][27][28]. Furthermore, conditionally automated vehicles may also be capable of managing certain noncritical driving situations without any driver intervention, such as overtaking or adaptation of the host vehicle's speed.…”
Section: 2mentioning
confidence: 99%
“…In semi automated driving, where the human's role alternates between driving and monitoring, such gamification could offer safety benefits as well. Miller et al (2016) found that people watching videos or reading were less drowsy than when overseeing the automated vehicle, indicating that additional stimuli can increase engagement in this context. Recently, Schroeter and Steinberger (2016) hypothesised that gamification and augmented reality may encourage voluntary attention and situational awareness in 67 After publication of this article, it has come to my attention that the phrasing of the term 'effects' may be misleading.…”
Section: Resultsmentioning
confidence: 99%